(untitled) (Third Sector Social Economic Review, 2021)
The of this study is to evaluate the airports that may have the status of large regional airports within the airport system in Turkey and to make an empirical analysis of whether Adana, Diyarbakır, Gaziantep, Kayseri, Samsun Çarşamba and Trabzon airports that may have this status can be privatized according to the results obtained. In the study; It has been determined that Adana, Trabzon, Kayseri, Gaziantep, Diyarbakır and Samsun Çarşamba airports have negative values according to the discounted cash flow method (DCF) and the reasons that may affect these results. Within the framework of these results, it has been evaluated and interpreted that the airports subject to the research can be privatized within the framework of PPP, although their values are negative according to the discounted cash flow method.